10th Anniversary of Biomedicines—Advances in Endothelial Dysfunction - Francesca Schinzari; Carmine Cardillo; Manfredi Tesauro (Biomedicines)
The vascular endothelium serves as an essential interface between tissues and the bloodstream, playing a key role in the regulation of blood flow [...]